Educação superior e autoavaliação : espaços contraditórios e transformadores em cursos de graduação da Universidade Federal de Mato Grosso - Bagatelli, Elizaine (2020)
This study focuses on the evaluation in Higher Education regarding self-assessment in undergraduate courses at the Federal University of Mato Grosso (UFMT). Taking into account that, the National System of Higher Education Evaluation (SINAES), conducting self-evaluation is considered a quality indicator of the undergraduate course, the UFMT, until the first term of 2019 had not yet established any internal policy to conduct this process. The courses that practiced it either did so as required by the external evaluation protocol carried out by the Anisio Teixeira National Institute for Educational Studies and Research (INEP), or because they understood they needed to improve the teaching level. Thus, the main objective of this research is to analyze if the undergraduate courses at the UFMT have developed self- evaluation as a transformational practice in the academic unit. This implies clarifying an issue: to what extent has self-evaluation become a practice in the scope of the undergraduate courses at the UFMT? The theoretical framework applied in this research discusses higher education based on the study of its policies, reforms and relationships; the studies and research trends in this level of education; national public policies to evaluate higher education, and conceptions on its quality, which is discussed as a subjective concept, related to perceptions, needs and results of each individual. For the investigation, a qualitative approach with content analysis was used, seeking to intertwine this with Pierre Bourdieu’s General Theory of Fields as a resource for data analysis. The research used as instruments for data collection the analysis of documents, semi-structured interviews and observation. The results found by this research show that, up to the end of the period for which there was available data, (2019/1), only one of the four undergraduate courses researched had a certain practice of performing self-evaluation, and in this course, the self-evaluative process is motivated and organized by the students. The academic management board of that unit uses the self-evaluation results as a regulatory means among the professors. As can be seen from the courses researched, self-evaluation as a practice in emancipatory, participative, and democratic perspectives was not observed. In this sense, the conclusion shows that, because it is believed and defended that self-evaluation has important and transformational formative potentialities for the undergraduate courses, it follows that this topic, needs to be debated and consolidated in the UFMT, both in terms of dynamics and form.